Lithium secondary battery and method for preparing lithium secondary battery
In the activation process of the lithium secondary battery, transferring lithium ions from the lithium metal layer of the positive electrode to the active material layer of the negative electrode, the problems of life reduction and heat generation caused by volume changes during the cycle of the lithium secondary battery are solved, and a longer battery life and lower heat risk are achieved.
Patent Information
- Application Number
- CN202380055951.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-28
AI Technical Summary
During the battery cycle, existing lithium secondary batteries have a rapid decrease in battery life due to excessive volume changes in silicon-based active material particles during the battery cycle, and there is a risk of excessive heat generation and ignition.
In the activation process of the battery, lithium ions are transferred from the lithium metal layer of the positive electrode to the active material layer of the negative electrode, and direct contact with the lithium metal layer at the negative electrode is avoided, thereby inhibiting the alloy reaction between lithium and silicon, and reducing the risk of heat generation and ignition.
This method effectively inhibits excessive volume changes of silicon-based active material particles, extends the life of the battery, and significantly reduces the risk of heat generation and fire during use of the battery.
Smart Images

Figure CN119547251A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the priority benefit of Korean Patent Application No. 10-2022-0106403, filed on August 24, 2022, the disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a lithium secondary battery and a method of manufacturing the lithium secondary battery, and relates to technical features such as the composition of a solid electrolyte layer provided on the surface of a negative electrode, the transfer of a lithium metal layer to a positive electrode, and charging at a specific current rate during an activation process. Background Art
[0004] Due to the rapid increase in the use of fossil fuels, the need for the use of alternative or clean energy has increased, and as part of this trend, power generation and power storage using an electrochemical reaction are the most active research fields.
[0005] Currently, a typical example of an electrochemical device using electrochemical energy may be a secondary battery, and there is a trend that its fields of use are increasingly expanding. In recent years, with the technological development and increasing demand for portable devices (such as portable computers, mobile phones, and cameras), the demand for ion secondary batteries as an energy source has increased significantly, and among these secondary batteries, a large amount of research has been conducted on lithium ion secondary batteries having a high energy density (i.e., high capacity), and they have been commercialized and widely used.
[0006] Generally, a lithium secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material, into which and from which lithium ions released from the positive electrode are intercalated and deintercalated, and a silicon-based active material particle having a large discharge capacity may be used as the negative electrode active material. The silicon-based active material particle may correspond to silicon (Si) or SiO x (0 < x < 2). The silicon-based active material particle has the advantages of a large theoretical capacity and low price. However, since the silicon-based active material particle has an excessive volume change during battery operation, its disadvantage is that as the battery is cycled, the life of the battery is rapidly reduced.
[0007] Therefore, in order to minimize the volume change of silicon-based active material particles, there is a method of using only a portion of the total capacity of silicon-based active material particles. To this end, a so-called pre-lithiation method is used, in which lithium ions are pre-embedded into a negative electrode containing silicon-based active material particles. Specifically, if lithium ions are embedded in the negative electrode by methods such as transferring lithium metal to the negative electrode, the total capacity of the negative electrode may be reduced to the level of reversible capacity due to the reaction of lithium ions at irreversible sites of the negative electrode. Therefore, since the amount of embedded lithium ions during battery operation can be appropriately reduced to the level required for battery operation, the volume change of silicon-based active material particles can be minimized.
[0008] However, in the process of pre-lithiation by placing lithium metal on the surface of the negative electrode, excessive heat is generated due to the alloy reaction between lithium and silicon, and the possibility of fire caused by the reaction between lithium and moisture is also increased. In addition, in the process of grooving and punching the negative electrode, the reaction area between lithium and silicon-based active materials may increase, thereby further increasing the possibility of fire. In addition, there is also the possibility of fire caused by pre-lithiation silicon-based active material particles.
[0009] Therefore, a new technology is needed that can improve the life of the battery by pre-intercalating lithium ions into the negative electrode before the battery is operated, while suppressing the possibility of excessive heat generation and fire. Summary of the invention
[0010] Technical issues
[0011] One aspect of the present invention provides a lithium secondary battery having improved lifespan characteristics and safety and low resistance.
[0012] Another aspect of the present invention provides a method for preparing a lithium secondary battery.
[0013] Technical Solution
[0014] According to one embodiment of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising:
[0015] A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector;
[0016] A negative electrode, the negative electrode comprising a negative electrode current collector, a negative electrode active material layer disposed on the negative electrode current collector, and a solid electrolyte layer disposed on the negative electrode active material layer;
[0017] A separator disposed between the positive electrode and the negative electrode; and
[0018] Electrolytes,
[0019] Here, the value of A according to Mathematical Formula 1 is greater than 10%.
[0020] [Mathematical formula 1]
[0021] {(F+C) / (F+C+G+M+E)}×100
[0022] Where F and C are the contents of fluorinated groups (unit: μg / cm 2 ) and carbonate group content (unit: μg / cm 2 ), which is confirmed by capillary electrophoresis (CE) analysis of the solid electrolyte layer, and
[0023] G, M and E are the contents of ethylene glycol groups (unit: μg / cm 2 ), methyl content (unit: μg / cm 2 ) and ethyl content (unit: μg / cm 2 ), which was confirmed by nuclear magnetic resonance (NMR) spectroscopy analysis of the solid electrolyte layer.
[0024] According to another embodiment of the present invention, there is provided a method for preparing a lithium secondary battery, the method comprising:
[0025] Step B1: preparing a preliminary lithium secondary battery, the preliminary lithium secondary battery comprising: a positive electrode, the positive electrode comprising a positive electrode collector and a positive electrode active material layer disposed on the positive electrode collector; a negative electrode, the negative electrode comprising a negative electrode collector, a negative electrode active material layer disposed on the negative electrode collector and a solid electrolyte layer disposed on the negative electrode active material layer; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, and
[0026] Step B2: activating the prepared lithium secondary battery,
[0027] The method for preparing the positive electrode comprises:
[0028] Step P1: Arranging a transfer stack on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, wherein the transfer stack comprises a substrate film and a lithium metal layer arranged on the substrate film, so that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0029] Step P2: rolling the positive electrode structure; and
[0030] Step P3: preparing a positive electrode by removing the substrate film from the transfer stack after the calendering,
[0031] Wherein step B2 includes charging the prepared lithium secondary battery by applying a current at a current rate of 0.1C to 1.0C to the prepared lithium secondary battery.
[0032] Beneficial Effects
[0033] In the positive electrode according to the present invention, a lithium metal layer is disposed on the positive electrode by a transfer method, and the lithium ions of the lithium metal layer are embedded in the positive electrode active material layer by a rolling process. If a preliminary lithium secondary battery is prepared by using a positive electrode prepared by the method as described above, and the preliminary lithium secondary battery is activated, the lithium ions embedded in the positive electrode are transferred to the negative electrode, so the lithium ions react and fill the irreversible sites of the negative electrode. Therefore, the amount of lithium ions embedded in the negative electrode during battery operation can be appropriately reduced to the level required for battery operation. Therefore, since the available range of the negative electrode capacity can be reduced while maintaining the battery capacity, the excessive volume change of the silicon-based active material particles can be suppressed, and the life characteristics of the battery can be improved.
[0034] In addition, since the lithium metal layer is not pre-lithiated by contacting the negative electrode with the lithium metal layer, but the lithium metal layer is transferred to the positive electrode and rolled, and then the lithium ions embedded in the positive electrode are transferred to the negative electrode in the activation process of the battery, the phenomenon of excessive heat generation due to the alloy reaction of lithium and silicon at the negative electrode can be avoided, and the possibility of fire caused by the reaction between lithium and moisture can be significantly reduced. In addition, since lithium ions are not embedded in the negative electrode during the slotting and punching of the negative electrode (due to no pre-lithiation), the possibility of fire during the slotting and punching can be significantly reduced.
[0035] In particular, in the activation process of the present invention, by adjusting the current rate applied during charging to an appropriate level, the cracking phenomenon of the negative electrode active material particles can be minimized. In addition, since the current rate applied during charging is adjusted to an appropriate level, the ratio of the fluorine-containing group and the carbonate group in the solid electrolyte layer can be high. Therefore, since the structural stability of the negative electrode can be maintained despite the large volume change of the negative electrode active material particles, and the solid electrolyte layer can be thin, the increase in battery resistance can be suppressed. Therefore, the initial capacity and life characteristics of the battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a schematic diagram illustrating step P1 in the method for preparing a positive electrode according to one embodiment of the present invention.
[0037] Figure 2 is a schematic diagram illustrating step P1 of using a transfer stack including a polymer layer in the method of preparing a positive electrode according to an embodiment of the present invention.
[0038] Figure 3is a schematic diagram illustrating step P2 in the method for preparing a positive electrode according to an embodiment of the present invention.
[0039] Figure 4 is a schematic diagram illustrating step P3 in the method for preparing a positive electrode according to an embodiment of the present invention. DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in more detail to allow a clearer understanding of the present invention.
[0041] It should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to better explain the present invention, these words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant fields and technical ideas of the present invention.
[0042] The terms used herein are only for the purpose of describing specific exemplary embodiments and are not intended to limit the present invention. In the specification, unless otherwise indicated, a term in the singular form may include a plural form.
[0043] It should also be understood that when used in this specification, the terms "comprises", "includes" or "has" indicate the presence of the described features, quantities, steps, elements or a combination thereof, but do not exclude the presence or increase of one or more other features, quantities, steps, elements or a combination thereof.
[0044] D in this manual 50 It can be defined as the particle size at which the cumulative volume in the particle size distribution curve is 50%. For example, D 50 This can be measured using laser diffraction, which can typically measure particle sizes from submicron to several millimeters and can produce highly reproducible and high-resolution results.
[0045] The X-ray diffraction (XRD) measurement in this specification is performed as follows.
[0046] The wavelength of X-rays generated by copper (Cu) Kα was used, and the wavelength (λ) of the light source was 0.15406 nm.
[0047] 1) Measurement equipment and conditions: Bruker D8 Endeavor (Cu target 40 kV, 40 mA, 1.54 Å) LynxEye position sensitive detector (4.1° slit)
[0048] 2) Experimental process
[0049] 2-1) Preparation. Cutting / cross section: Prepare the sample by cutting it to the size of the sample holder.
[0050] 2-2) Preparation. Sample mounting: The sample (positive electrode) was adhered to a glass plate using a double-sided tape so that there was no gap therebetween, and then mounted using rubber clay and a fixture formed of PMMA.
[0051] 2-3) Powder XRD (Bruker D8 Endeavor): The fixed divergence slit (FDS) was adjusted to 0.5° according to the sample size, and the powder XRD was measured every 0.0156° in the 2θ range of 10° to 125° for 0.3 seconds.
[0052] 2-4) XRD phase analysis: The phases present in the sample are identified by comparing them with a database (PDF).
[0053] 2-5) Rietveld analysis: Rietveld refinement is performed using a complete structural model of the phases present in the sample.
[0054] In this specification, the measurement conditions of laser induced breakdown spectroscopy (LIBS) analysis are as follows. For LIBS, J200 (Tandem-LA-LIBS) of Applied Spectra, Inc. was used. Then, when the instrument temperature reached -20°C, measurement was performed under the following conditions.
[0055] - Laser power: 20%
[0056] - Spot size: 150μm
[0057] - Number of irradiations: 15 irradiations
[0058] - Number of light spots: 6×6
[0059] - Gate delay: 1μsec
[0060] - Rep rate: 5Hz
[0061] - Analysis Mode: Mapping and Deep Profiling Experiments
[0062] In this specification, the ethylene glycol content, ethyl content, and methyl content in the solid electrolyte layer are determined by confirming the peak integral values of the corresponding functional groups measured by 1H-NMR analysis and considering the molecular weights of ethylene glycol, ethanol, and methanol, respectively. In this article, 1H-NMR analysis was performed using a 500 MHz Varian, Inc. 1 HNMR was performed.
[0063] In this specification, the content of the fluorine-containing group and the content of the carbonate group are each confirmed by capillary electrophoresis (CE) analysis. Specifically, the analysis is performed after running the instrument (MDQ plus of AB SCIEX Pte. Ltd.). In this case, the presence of MeOD (methanol d4) extraction solution absorbs CO2 in the atmosphere and increases CO3 2- The sample was stored in a G / B (glove box) during the measurement, and then taken out to the atmosphere and analyzed immediately. The content of the fluorine-containing group and the content of the carbonate group were determined by the measured CE area.
[0064] Used for 1 The samples for H-NMR and CE analysis were prepared as follows. The lithium secondary battery prepared by activation was fully charged and then discharged from 4.2V to 2.5V for initial discharge. Then, only the negative electrode was separated and washed with dimethyl carbonate (DMC). The solid electrolyte layer extracted from the negative electrode was dissolved in MeOD (methanol d4) and then used as a sample for 1 H-NMR measurement. Then, the sample was dissolved in heavy water again and used as a sample for CE analysis.
[0065] <Lithium Secondary Battery>
[0066] A lithium secondary battery according to one embodiment of the present invention includes:
[0067] A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector;
[0068] A negative electrode, the negative electrode comprising a negative electrode current collector, a negative electrode active material layer disposed on the negative electrode current collector, and a solid electrolyte layer disposed on the negative electrode active material layer;
[0069] A separator disposed between the positive electrode and the negative electrode; and
[0070] Electrolytes,
[0071] Here, the value of A according to the following mathematical formula 1 can be greater than 10%.
[0072] [Mathematical formula 1]
[0073] A = {(F+C) / (F+C+G+M+E)}×100
[0074] Where F and C are the contents of fluorinated groups (unit: μg / cm 2 ) and carbonate group content (unit: μg / cm 2), which is confirmed by capillary electrophoresis analysis of the solid electrolyte layer, and
[0075] G, M and E are the contents of ethylene glycol groups (unit: μg / cm 2 ), methyl content (unit: μg / cm 2 ) and ethyl content (unit: μg / cm 2 ), which was confirmed by nuclear magnetic resonance (NMR) spectroscopy analysis of the solid electrolyte layer.
[0076] (1) Positive electrode
[0077] The positive electrode may include a positive electrode active material layer. The positive electrode active material layer itself may constitute the positive electrode, but the positive electrode active material layer may be provided on a positive electrode current collector.
[0078] The positive electrode current collector is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can typically have a thickness of 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. The positive electrode current collector can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0079] The positive electrode active material layer may be provided on one surface or both surfaces of the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material.
[0080] The positive electrode active material is a material in the form of particles that can cause an electrochemical reaction, wherein it can be a lithium transition metal oxide. For example, the positive electrode active material can include at least one selected from the group consisting of: a layered compound such as lithium cobalt oxide or lithium nickel oxide substituted with at least one transition metal; a lithium manganese oxide substituted with at least one transition metal; a lithium nickel cobalt manganese composite oxide composed of Li 1+x [Ni a Co b Mn c M 1 (1-a-b-c) ]O (2-d) A d (Among them, M 1is at least one selected from the group consisting of aluminum (Al), magnesium (Mg), chromium (Cr), titanium (Ti), silicon (Si), and yttrium (Y), A is at least one selected from the group consisting of fluorine (F), phosphorus (P), and chlorine (Cl), and -0.5 ≤ x ≤ 0.5, 0.1 ≤ a ≤ 1, 0.05 ≤ b ≤ 0.5, 0.05 ≤ c ≤ 0.5, 0 ≤ d ≤ 0.2, and 0 < a + b + c ≤ 1); a lithium nickel-based oxide represented by Li[Ni 1-y M 2 y O2 (where M 2 can be at least one selected from the group consisting of cobalt (Co), manganese (Mn), Al, copper (Cu), iron (Fe), Mg, boron (B), Cr, zinc (Zn), and gallium (Ga), and 0.01 ≤ y ≤ 0.7); and an olivine-based lithium metal phosphate represented by Li 1+z [M 3 1-q M 4 q PO 4-r X r (where M 3 is at least one selected from the group consisting of Fe, Mn, Co, and nickel (Ni), M 4 is at least one selected from the group consisting of Al, Mg, and Ti, X is at least one selected from the group consisting of F, sulfur (S), and nitrogen (N), and -0.5 ≤ z ≤ 0.5, 0 ≤ q ≤ 0.5, and 0 ≤ r ≤ 0.1).
[0081] Specifically, the positive electrode active material may include a layered lithium nickel-based transition metal composite oxide, and the lithium nickel-based transition metal composite oxide may include a compound of Chemical Formula 1 below, and more specifically may be a compound of Chemical Formula 1 below.
[0082] [Chemical Formula 1]
[0083] Li 1+x [Ni a Co b Mn c M 1 (1-a-b-c) O (2-d) A d
[0084] In Chemical Formula 1, M 1 is at least one selected from the group consisting of Al, Mg, Cr, Ti, Si, and Y, and may specifically be Al.
[0085] A is at least one selected from the group consisting of F, P, and Cl, and may specifically be F.
[0086] x can satisfy -0.5 ≤ x ≤ 0.5, specifically, -0.3 ≤ x ≤ 0.3.
[0087] a can satisfy 0.6 ≤ a < 1, specifically, 0.7 ≤ a ≤ 0.9.
[0088] b can satisfy 0.03 ≤ b ≤ 0.1, specifically, 0.05 ≤ b ≤ 0.1.
[0089] c can satisfy 0.03 ≤ c ≤ 0.1, specifically, 0.05 ≤ c ≤ 0.1.
[0090] d can satisfy 0 ≤ d ≤ 0.1, specifically, 0.01 ≤ d ≤ 0.05.
[0091] a, b, and c satisfy 0 < a + b + c ≤ 1, specifically, a + b + c = 1.
[0092] The layered lithium nickel-based transition metal composite oxide can be in the form of particles.
[0093] The layered lithium nickel-based transition metal composite oxide can be in the form of secondary particles in which a plurality of primary particles are combined with each other. Specifically, the compound of Chemical Formula 1 can be in the form of secondary particles in which 10 or more primary particles are combined with each other. Therefore, there is an effect that lithium can be uniformly inserted into and extracted from the positive electrode active material.
[0094] The D of the layered lithium nickel-based transition metal composite oxide 50 can be 5 μm to 15 μm, particularly 7 μm to 12 μm, more particularly 9 μm to 10 μm. Since the positive electrode slurry is easily dispersed when the above range is satisfied, uniform coating of the positive electrode active material layer is possible.
[0095] The content of the positive electrode active material in the positive electrode active material layer can be 90% by weight to 99% by weight, particularly 92% by weight to 99% by weight, more particularly 95% by weight to 98.5% by weight.
[0096] The positive electrode active material layer may also include a positive electrode binder. The positive electrode binder improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples of the binder may be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.
[0097] The positive electrode binder may be contained in the positive electrode active material layer in an amount of 0.5 wt % to 5.0 wt %, specifically 1.0 wt % to 2.5 wt %, and more specifically 1.0 wt % to 2.0 wt %.
[0098] The positive electrode active material layer may also include a positive electrode conductive material. The positive electrode conductive material is used to provide conductivity to the electrode, wherein any conductive material may be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of the positive electrode conductive material may be graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof may be used.
[0099] The positive electrode conductive material may be contained in the positive electrode active material layer in an amount of 0.5 to 30.0 wt %, specifically 0.5 to 10.0 wt %, and more specifically 1.0 to 4.0 wt %.
[0100] The positive electrode active material layer may further include a lithium byproduct. The lithium byproduct corresponds to a byproduct formed by transferring a lithium metal layer onto the positive electrode active material layer and rolling it during the preparation of the positive electrode. Specifically, the positive electrode active material layer may include any one selected from the group consisting of Li3N, Li2CO3 and LiOH.
[0101] The positive electrode may satisfy the following Mathematical Formula 3.
[0102] [Mathematical formula 3]
[0103] 1.2 ≤ I
[003] / I
[200] ≤ 2.0
[0104] In mathematical formula 3, I
[003] is the integrated value of the maximum peak appearing in the 2θ range of 17.0° to 19.0° during X-ray diffraction (XRD) measurement of the surface of the positive electrode active material layer, and
[0105] I
[200] is an integrated value of the maximum peak appearing in the 2θ range of 43° to 45° during the XRD measurement of the surface of the positive electrode active material layer.
[0106] Specifically, the 2θ range where the maximum peak appears may be 17.5° to 18.5°, and may be 17.5° to 18.2°.
[200] It is an integrated value of a maximum peak appearing in a 2θ range of 43° to 45° when the XRD measurement is performed on the surface of the positive electrode active material layer, and the 2θ range in which the maximum peak appears may be 43.5° to 44.5°, and may be 43.7° to 44.3°.
[0107] In addition, according to one embodiment of the present invention, I of Mathematical Formula 3
[003] / I
[200] It may preferably be 1.21 or more, 1.22 or more, 1.23 or more, or 1.24 or more, and may preferably be 1.80 or less, 1.70 or less, 1.65 or less, 1.60 or less, or 1.58 or less.
[0108] When the above range is met, since a sufficient amount of lithium can be supplied to the negative electrode during the activation process, the life characteristics of the battery can be improved. In addition, since the amount of lithium byproducts in the positive electrode is small, the capacity of the positive electrode and the long-term life characteristics of the battery can be good.
[0109] The positive electrode may further include a lithium metal layer disposed on the positive electrode active material layer. The lithium metal layer plays a role in supplying lithium ions to the positive electrode active material layer. Specifically, the positive electrode active material layer may be disposed between the positive electrode current collector and the lithium metal layer. The lithium metal layer may be in contact with the positive electrode active material layer. The lithium metal layer includes solid-phase lithium metal, and the lithium metal layer may be specifically formed of solid-phase lithium metal.
[0110] The positive electrode may further include a polymer layer disposed on the positive electrode active material layer. The polymer layer may play a role in effectively peeling off the lithium metal layer from the transfer stack and allowing the lithium metal layer to be easily transferred to the positive electrode active material layer during the preparation of the positive electrode. That is, the polymer layer may be separated from the transfer stack together with the lithium metal layer to be disposed on the positive electrode active material layer. The polymer layer may be in contact with the positive electrode active material layer, and alternatively, the lithium metal layer may be present between the polymer layer and the positive electrode active material layer.
[0111] The polymer layer may be at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene and polycarbonate. Therefore, in a secondary battery comprising the positive electrode, since the polymer layer can be dissolved in the electrolyte contained in the secondary battery, the resistance of the battery can be prevented from increasing. In particular, the polymer layer may include PMMA, and in this case, the above-mentioned effect can be further improved.
[0112] In the positive electrode, the positive electrode active material layer may have a porosity of 10% to 40%, particularly 15% to 35%, and more particularly 25% to 30%. In this case, no additional thickness change may occur during calendering. The porosity may be confirmed by measuring the apparent density and true density of the positive electrode active material layer.
[0113] The loading capacity of the positive electrode active material layer can be 3 mAh / cm 2 Up to 5.5mAh / cm 2 range, and may be specifically within 4 mAh / cm 2 Up to 5mAh / cm 2 within the range.
[0114] (2) Negative electrode
[0115] The negative electrode may include a negative electrode current collector, a negative electrode active material layer disposed on the negative electrode current collector, and a solid electrolyte layer (SEI) disposed on the negative electrode active material layer.
[0116] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing adverse chemical changes in the battery, and, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy can be used. In addition, the negative electrode current collector can typically have a thickness of 3 μm to 500 μm, and, similar to the positive electrode current collector, fine concavoconvexities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0117] The negative electrode active material layer may be disposed on one surface or both surfaces of the negative electrode current collector. The negative electrode active material layer may include negative electrode active material particles.
[0118] The negative electrode active material particles may include silicon-based negative electrode active material particles. The silicon-based negative electrode active material particles may include Si and SiO x At least one of (0<x<2).
[0119] The Si is a silicon particle, wherein it can be a silicon particle (a particle formed of silicon), that is, so-called pure silicon. The silicon particle can effectively improve the capacity of the negative electrode. The SiO x (0<x<2) may be a form containing Si and SiO2, and the Si may constitute a phase. That is, x corresponds to the phase contained in the SiO2. x The silicon-based composite particles contain the SiO x In the case of (0<x<2), the discharge capacity of the secondary battery can be improved.
[0120] If an activation process is performed during the preparation of the lithium secondary battery of the present invention, since the predetermined lithium ions are transferred from the positive electrode to the silicon-based negative electrode active material of the negative electrode, the excessive volume change of the silicon-based active material during the battery operation can be suppressed, and the life characteristics of the battery can be improved. In addition, since the separate lithium metal layer is not transferred to the negative electrode, the negative electrode and the lithium metal layer are not in contact with each other, and the lithium ions are not directly embedded in the negative electrode from the lithium metal layer. Therefore, the phenomenon of excessive heat generation caused by the alloy reaction of lithium and silicon at the negative electrode can be avoided, and the possibility of fire caused by the reaction between lithium and moisture can be significantly reduced. In addition, since lithium ions are not embedded in the negative electrode during the slotting and punching of the negative electrode (due to no pre-lithiation), the possibility of fire during the slotting and punching can be significantly reduced. That is, in the present invention, when the negative electrode active material particles contain the silicon-based active material particles, this has greater significance.
[0121] The negative electrode active material may further include a carbon-based negative electrode active material. The carbon-based negative electrode active material may include at least one selected from the group consisting of artificial graphite, natural graphite, and graphitized mesophase carbon microbeads.
[0122] The negative electrode active material may be contained in an amount of 70 wt % to 98 wt %, for example 80 wt % to 90 wt % in the negative electrode active material layer.
[0123] The negative electrode active material layer may further include a negative electrode binder. The negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylate, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials whose hydrogen is replaced by lithium (Li), sodium (Na) or calcium (Ca), or various copolymers thereof.
[0124] The negative electrode binder may be contained in an amount of 5 wt % to 30 wt %, for example 10 wt % to 20 wt % in the negative electrode active material layer.
[0125] The negative electrode active material layer may further include a negative electrode conductive material. The negative electrode conductive material is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and for example, conductive materials such as: graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbon powders; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0126] The negative electrode conductive material may be contained in the negative electrode active material layer in an amount of 1 wt % to 15 wt %, for example 5 wt % to 10 wt %.
[0127] The negative electrode active material layer may have a porosity of 30% to 50%, specifically 35% to 48%. In this case, although the volume change of the negative electrode active material is large, the negative electrode structure can still be maintained, and the lithium transferred from the positive electrode can be effectively embedded. The porosity can be confirmed by measuring the apparent density and true density of the negative electrode active material layer.
[0128] The loading capacity of the negative electrode active material layer can be 7 mAh / cm 2 Up to 14mAh / cm 2 range, and may be specifically within 7.5 mAh / cm 2 Up to 11.9 mAh / cm 2 within the range.
[0129] The solid electrolyte layer may be disposed on the negative electrode active material layer. Specifically, the negative electrode active material layer may be disposed between the solid electrolyte layer and the negative electrode current collector. Since the solid electrolyte layer suppresses an excessive decomposition reaction of the electrolyte and allows lithium ions to pass but does not allow electrons to pass, it plays a role in promoting the operation of the battery.
[0130] The solid electrolyte layer may include an organic component and an inorganic component.
[0131] The organic component may include a compound of Chemical Formula 1 below.
[0132] [Chemical formula 1]
[0133]
[0134] In Chemical Formula 1, R may be at least one selected from an alkyl group having 1 to 4 carbon atoms and an alkanediol group having 1 to 4 carbon atoms. Specifically, R may be at least one selected from the group consisting of a methyl group, an ethyl group, and an ethylene glycol group.
[0135] The inorganic component may include at least one selected from the group consisting of LiF and Li2CO3.
[0136] (3) Diaphragm
[0137] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as the separator without particular limitation, as long as it is typically used for secondary batteries, and in particular, preferably has high moisture retention for electrolytes and has low resistance to the transfer of electrolyte ions. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure having two or more layers thereof. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed by a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a monolayer or multilayer structure can be optionally used.
[0138] (4) Electrolytes
[0139] The electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used to prepare a lithium secondary battery, but the present invention is not limited thereto.
[0140] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0141] Examples of the non-aqueous organic solvent may be aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0142] Especially, ethylene carbonate and propylene carbonate (cyclic carbonate in carbonate organic solvent) have high dielectric constant and dissociate lithium salt well in electrolyte owing to high viscosity organic solvent, therefore, can preferably use cyclic carbonate.Because when described cyclic carbonate and low-viscosity low dielectric constant linear carbonate such as dimethyl carbonate and diethyl carbonate are mixed with suitable ratio, can prepare electrolyte with high conductivity, therefore such combination use can be more preferred.
[0143] A lithium salt can be used as the metal salt, and the lithium salt is a substance that can be easily dissolved in the non-aqueous electrolyte, wherein, for example, at least one selected from the group consisting of the following can be used as the anion of the lithium salt: - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - 、CF3CF2SO3-、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0144] For the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity and improving the discharge capacity of the battery, the electrolyte may further include at least one additive, such as a halogenated alkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, (condensed) glycol dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, in addition to containing the above-mentioned electrolyte components.
[0145] The A value of the lithium secondary battery according to Math. 1 may be 10% or more, specifically 10% to 20%, more specifically 11% to 15%, for example 13.5% to 15%.
[0146] [Mathematical formula 1]
[0147] A = {(F+C) / (F+C+G+M+E)}×100
[0148] Where F and C are the contents of fluorinated groups (unit: μg / cm 2 ) and carbonate group content (unit: μg / cm 2 ), which was confirmed by capillary electrophoresis analysis of the solid electrolyte layer, and
[0149] G, M and E are the contents of ethylene glycol groups (unit: μg / cm 2 ), methyl content (unit: μg / cm 2 ) and ethyl content (unit: μg / cm 2 ), which was confirmed by nuclear magnetic resonance (NMR) spectroscopy analysis of the solid electrolyte layer.
[0150] In the case where the A value is less than 10%, since the solid electrolyte layer cannot effectively suppress excessive volume expansion of the negative electrode active material particles, the initial capacity of the battery may be reduced due to additional lithium side reactions.
[0151] In the process of preparing the lithium secondary battery of the present invention, if the rate of the current applied during charging is adjusted to 0.1C to 1.0C, the cracking phenomenon of the negative electrode active material particles can be minimized by the lithium ions transferred from the positive electrode to the negative electrode active material layer. Therefore, since the solid electrolyte layer formed on the negative electrode active material layer can contain more inorganic components such as LiF and Li2CO3 than the organic components such as the compound of Chemical Formula 1, the A value of Mathematical Formula 1 can be 10% or more. Therefore, since the solid electrolyte layer can be stably formed, damage to the negative electrode active material layer can be effectively prevented, and additional side reactions of the electrolyte can be effectively suppressed.
[0152] The L value of the lithium secondary battery according to Math. 2 may be 45% or more, specifically 45% to 80%, more specifically 55% to 70%, for example 63% to 68%.
[0153] [Mathematical formula 2]
[0154] L = L2 / L1
[0155] where L1 and L2 are the integral values of the lithium peak in the graph obtained by laser induced breakdown spectroscopy (LIBS),
[0156] wherein L1 is measured at the interface between the negative electrode active material layer and the negative electrode current collector, and
[0157] L2 is measured at a point at a distance of 20% of the thickness of the negative electrode active material layer in the thickness direction from the interface between the negative electrode active material layer and the solid electrolyte layer.
[0158] Since the current is applied at an appropriate current rate during the activation process, the lithium ions can be uniformly distributed in the negative electrode active material layer, so the A value according to Mathematical Formula 1 is satisfied, and at the same time the L value can be 45% or more. Therefore, the solid electrolyte layer can be uniformly formed on the negative electrode active material layer, the formation of lithium byproducts in the negative electrode can be reduced, and the initial capacity and life characteristics of the battery can be improved.
[0159] <Method for preparing lithium secondary battery>
[0160] According to another embodiment of the present invention, a method for preparing a lithium secondary battery includes:
[0161] Step B1: preparing a preliminary lithium secondary battery, the preliminary lithium secondary battery comprising: a positive electrode, the positive electrode comprising a positive electrode collector and a positive electrode active material layer disposed on the positive electrode collector; a negative electrode, the negative electrode comprising a negative electrode collector, a negative electrode active material layer disposed on the negative electrode collector and a solid electrolyte layer disposed on the negative electrode active material layer; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, and
[0162] Step B2: activating the prepared lithium secondary battery,
[0163] The method for preparing the positive electrode comprises:
[0164] Step P1: Arranging a transfer stack on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, wherein the transfer stack comprises a substrate film and a lithium metal layer arranged on the substrate film, so that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other;
[0165] Step P2: rolling the positive electrode structure; and
[0166] Step P3: preparing a positive electrode by removing the substrate film from the transfer stack after the calendering,
[0167] Step B2 may include charging the prepared lithium secondary battery by applying a current at a current rate of 0.1C to 1.0C to the prepared lithium secondary battery.
[0168] Since the positive electrode, the negative electrode, the separator, and the electrolyte are the same as those of the above-described embodiment, description thereof will be omitted.
[0169] (1) Step B1
[0170] In step B1, the prepared lithium secondary battery may include a positive electrode and a negative electrode. Specifically, the prepared lithium secondary battery may include a positive electrode, a negative electrode, a separator and an electrolyte. Specifically, the positive electrode and the negative electrode are separated from each other and stacked by a separator disposed therebetween, and may be impregnated with the electrolyte. The negative electrode before the activation process may be a prepared negative electrode, and means a state in which lithium ions have not yet been embedded. The prepared lithium secondary battery refers to a battery before the activation process.
[0171] 1) Step P1
[0172] refer to Figure 1, the transfer stack 300 may include a substrate film 310 and a lithium metal layer 320 disposed on the substrate film 310. The substrate film 310 may be used without limitation as long as it is a material that can withstand the high temperature conditions present in the process of depositing the lithium metal layer 320 on the substrate film 310. Specifically, the substrate film may include at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate.
[0173] The lithium metal layer may be provided on the substrate film. The lithium metal layer plays a role in supplying lithium ions to the preliminary positive electrode active material layer. The lithium metal layer contains solid-phase lithium metal, and the lithium metal layer may be specifically formed of solid-phase lithium metal.
[0174] In the transfer stack, the thickness of the lithium metal layer may be 1 μm to 10 μm, particularly 3 μm to 9 μm, and more particularly 4 μm to 6.5 μm. When the above range is met, the degree of cracking of the positive electrode active material particles on the positive electrode surface may be reduced, thereby suppressing the reduction in the initial capacity of the battery.
[0175] The loading capacity of the lithium metal layer (unit: mAh / cm 2 ) may be the loading amount of the preliminary positive electrode active material layer (unit: mAh / cm 2 ) is 4% to 40%, and may be specifically 12% to 35%, more specifically 20% to 30%. When the above range is met, since the generation of by-products is small and lithium can be easily embedded in the positive electrode active material, the target lithium embedding capacity can be easily achieved.
[0176] In step P1, refer to Figure 1 , a preliminary positive active material layer 120 ′ is disposed on the positive current collector 110 , and a transfer stack 300 may be disposed on the preliminary positive active material layer 120 ′ to form a positive electrode structure 400 such that the lithium metal layer 320 and the preliminary positive active material layer are in contact with each other.
[0177] Herein, the positive electrode current collector 110 is the same as the positive electrode current collector described in the embodiment related to the above-mentioned positive electrode.
[0178] refer to Figure 2, the transfer stack 300 may further include a polymer layer 330. The polymer layer 330 may be disposed between the substrate film 310 and the lithium metal layer 320. The polymer layer may effectively peel off the lithium metal layer from the transfer stack during the preparation of the positive electrode and allow the lithium metal layer to be easily transferred to the positive electrode active material layer. That is, the polymer layer may be separated from the transfer stack together with the lithium metal layer to be disposed on the positive electrode active material layer. The polymer layer may be in contact with the positive electrode active material layer, and alternatively, the lithium metal layer may be present between the polymer layer and the positive electrode active material layer.
[0179] The polymer layer may be at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methyl methacrylate) (PMMA), polypropylene, polyethylene and polycarbonate. Therefore, in a secondary battery comprising the positive electrode, since the polymer layer can be dissolved in the electrolyte contained in the secondary battery, the resistance of the battery can be prevented from increasing. In particular, the polymer layer may include PMMA, and in this case, the above-mentioned effect can be further improved.
[0180] The thickness of the polymer layer may be 0.1 μm to 10 μm, particularly 0.5 μm to 5 μm, and more particularly 1 μm to 2.5 μm. When the above range is met, the lithium metal layer may be easily transferred to the positive electrode active material layer, and a reverse transfer phenomenon in which the positive electrode active material layer is transferred to the transfer stack may be prevented.
[0181] 2) Step P2
[0182] refer to Figure 3 , in step P2, the prepared positive electrode structure 400 can be calendered. The calendering can be performed by a rolling method. Specifically, by two rollers R spaced apart from each other by a predetermined space in the vertical direction, pressure can be applied to the positive electrode structure 400 passing through the space in the vertical direction, and the pressure can be a linear pressure. Through the calendering process, at least a portion of the lithium ions of the lithium metal layer contained in the transfer stack can be embedded in the preliminary positive electrode active material layer. In this process, the preliminary positive electrode active material layer can become a positive electrode active material layer. In Figure 3 and Figure 4 , the lithium metal layer is shown to be included in the positive electrode, but in the case where the entire lithium metal layer is embedded in the preliminary positive electrode active material layer during the rolling process, the lithium metal layer may not exist as a separate layer.
[0183] The pressure applied to the positive electrode structure during the rolling process may be in the range of 10 kgf / cm to 90 kgf / cm, particularly 15 kgf / cm to 80 kgf / cm, and more particularly 20 kgf / cm to 40 kgf / cm. When the above range is satisfied, the amount of lithium transferred to the negative electrode during the activation process may be sufficient, and the cracking phenomenon of the positive electrode active material particles and the formation of the lithium byproducts may be suppressed to improve the positive electrode capacity and the life characteristics of the battery.
[0184] 3) Step P3
[0185] refer to Figure 4 In step P3, after the rolling in step P2, the positive electrode 100 can be prepared by removing the substrate film 310 from the transfer stack. In the case where the polymer layer 330 is disposed between the substrate film 310 and the lithium metal layer 320, the substrate film 310 can be more easily removed by the polymer layer 330.
[0186] In addition, the method for preparing a positive electrode may further include step P4: leaving the prepared positive electrode to stand (placed alone) for 1 minute to 600 minutes, specifically 1 minute to 30 minutes. Step P4 may be performed after step P2. Specifically, step P4 may be performed in at least one of "between step P2 and step P3" and "immediately after step P3". Since step P4 can effectively release the reaction heat generated by the reaction of the lithium metal layer and the prepared positive electrode active material layer in step P2, thereby uniformly embedding lithium into the positive electrode, it has the effect of reducing the generation of by-products.
[0187] The method for preparing a positive electrode may further include step P4: leaving the prepared positive electrode to stand (placed alone) for 1 minute to 600 minutes, specifically 1 minute to 30 minutes. Step P4 may be performed after step P2. Specifically, step P4 may be performed in at least one of "between step P2 and step P3" and "immediately after step P3". Since step P4 can effectively release the reaction heat generated by the reaction of the lithium metal layer and the prepared positive electrode active material layer in step P2, lithium is uniformly embedded in the positive electrode, thereby having the effect of reducing the generation of by-products.
[0188] Since the prepared positive electrode is the same as the positive electrode of the above embodiment, a detailed description thereof will be omitted.
[0189] (2) Step B2
[0190] Step B2 may include charging the preliminary lithium secondary battery by applying a current at a current rate of 0.1C to 1C to the preliminary lithium secondary battery.
[0191] Specifically, step B2 corresponds to the so-called “activation process.” In step B2, the preliminary lithium secondary battery is charged and discharged, whereby excess lithium ions formed by the lithium metal layer and present in the positive electrode active material layer can move to the negative electrode active material layer to achieve pre-lithiation of the negative electrode.
[0192] When charging the prepared lithium secondary battery in step B2, a current may be applied to the prepared lithium secondary battery at a current rate of 0.1C to 1C, and specifically, the current rate may be in the range of 0.1C to 0.7C, more specifically 0.1C to 0.3C. In the case where the current rate is less than 0.1C, it is difficult to improve the life characteristics of the battery due to the insufficient amount of lithium ions transferred from the positive electrode active material layer to the negative electrode active material layer. In the case where the current rate is greater than 1C, the initial capacity and life characteristics of the battery may be reduced due to excessive occurrence of cracking of the negative electrode active material particles and increased formation of lithium byproducts in the negative electrode.
[0193] Step B2 may be performed at a temperature of 15° C. to 85° C., and specifically may be performed at a temperature of 20° C. to 60° C., more specifically 20° C. to 40° C. When the above range is satisfied, the initial resistance of the battery may be reduced because the ion conductivity of the electrolyte is improved and the ratio of the inorganic component in the solid electrolyte layer is high.
[0194] According to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit cell and a battery pack including the battery module are provided. Since the battery module and the battery pack include lithium secondary batteries having high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0195] Hereinafter, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are only provided to illustrate the present invention, and various modifications and changes can be made within the scope and technical spirit of the present invention. These modifications and changes fall within the scope of the claims included herein.
[0196] Examples and Comparative Examples
[0197] Example 1: Preparation of lithium secondary battery
[0198] (1) Preparation of positive electrode
[0199] A transfer stack was prepared, the transfer stack comprising a PET film (substrate film), a polymer layer (2.5 μm thick) formed of PMMA disposed on the PET film, and a lithium metal layer (6 μm thick, with a loading of 1.24 mAh / cm) formed of solid-phase lithium metal disposed on the polymer layer. 2 ).
[0200] Will Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 is used as a positive electrode active material. The positive electrode active material is a plurality of (more than 10) Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 primary particles are combined with each other to form secondary particles, and the average particle size of the secondary particles is D 50 A positive electrode was prepared, the positive electrode comprising a prepared positive electrode active material layer and an aluminum foil (thickness: 12 μm) as a positive electrode current collector, the prepared positive electrode active material layer comprising the positive electrode active material, PVdF as a positive electrode binder, and carbon nanotubes as a positive electrode conductive material in a weight ratio of 98:1:1. The loading capacity of the prepared positive electrode active material layer was 4.5 mAh / cm 2 And the thickness is 140 μm.
[0201] The transfer stack is disposed on the preliminary positive electrode active material layer so that the lithium metal layer is in contact with the preliminary positive electrode active material layer.
[0202] Then, the positive electrode on which the transfer stack is arranged is rolled by a roller pressing method and then left to stand for 24 hours. The pressure during the rolling is 20kgf / cm. Thus, the lithium ions of the lithium metal layer are embedded in the prepared positive electrode active material layer to form a positive electrode active material layer. Then, the substrate film is removed, and the rolled positive electrode is left to stand for 10 minutes to prepare a positive electrode comprising the positive electrode collector, the positive electrode active material layer and the polymer layer.
[0203] (2) Preparation of lithium secondary batteries
[0204] The average particle size D 50 Silicon particles with a diameter of 5 μm are used as negative electrode active materials. A negative electrode is prepared, the negative electrode comprising a preliminary negative electrode active material layer, the preliminary negative electrode active material layer comprising the negative electrode active material, CMC as a negative electrode binder, and carbon nanotubes as a negative electrode conductive material in a weight ratio of 80:10:10. The loading amount of the preliminary negative electrode active material layer is 10 mAh / cm 2 And the thickness is 75 μm.
[0205] The positive electrode prepared in (1), the negative electrode and the porous polyethylene separator were assembled using a winding method, and a preliminary lithium secondary battery was prepared by injecting an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio) and lithium hexafluorophosphate (LiPF6 1 M) into the assembled battery and leaving the assembled battery alone for 48 hours.
[0206] (3) Preparation of lithium secondary batteries
[0207] The activation process was performed by charging the prepared lithium secondary battery to 4.2 V at 25° C. with a current at a current rate of 0.1 C, and then discharging it to 2.5 V at 0.5 C.
[0208] Examples 2 to 5 and Comparative Examples 1 and 2: Preparation of lithium secondary batteries
[0209] Lithium secondary batteries of Examples 2 to 5 and Comparative Examples 1 and 2 were prepared in the same manner as Example 1, except that the rate of current applied during charging (charging in the activation process) of the preliminary lithium secondary batteries was changed as shown in Table 1.
[0210] Comparative Example 3: Preparation of lithium secondary battery
[0211] A transfer stack was prepared, the transfer stack comprising a PET film (substrate film), a polymer layer (2.5 μm thick) formed of PMMA disposed on the PET film, and a lithium metal layer (6 μm thick, with a loading of 1.24 mAh / cm) formed of solid-phase lithium metal disposed on the polymer layer. 2 ).
[0212] The average particle size D 50 A negative electrode is prepared, wherein the negative electrode comprises a preliminary negative electrode active material layer, wherein the preliminary negative electrode active material layer comprises the negative electrode active material, carboxymethyl cellulose (CMC) as a negative electrode binder, and carbon nanotubes as a negative electrode conductive material in a weight ratio of 80:10:10. The loading capacity of the preliminary negative electrode active material layer is 10 mAh / cm 2 And the thickness is 75 μm.
[0213] The transfer stack is disposed on the preliminary negative electrode active material layer so that the lithium metal layer is in contact with the preliminary negative electrode active material layer.
[0214] Then, the negative electrode on which the transfer stack was placed was rolled by a roll pressing method and then left to stand for 24 hours. Thus, the lithium ions of the lithium metal layer were embedded in the preliminary negative electrode active material layer to form a negative electrode active material layer. The pressure during the rolling was 50 kgf / cm.
[0215] Then, a negative electrode including the negative electrode current collector, the negative electrode active material layer, and the polymer layer is prepared by removing the base film.
[0216] (2) Preparation of lithium secondary batteries
[0217] Will Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 is used as a positive electrode active material. The positive electrode active material is a plurality of (more than 10) Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 primary particles are combined with each other to form secondary particles, and the average particle size of the secondary particles is D 50 A positive electrode was prepared, wherein a preliminary positive electrode active material layer containing the positive electrode active material, PVdF as a positive electrode binder, and carbon nanotubes as a positive electrode conductive material in a weight ratio of 98:1:1 was arranged on an aluminum foil (thickness: 12 μm). The loading capacity of the preliminary positive electrode active material layer was 4.5 mAh / cm 2 And the thickness is 140 μm.
[0218] The negative electrode prepared in (1), the positive electrode and the porous polyethylene separator were assembled using a winding method, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1 / 2 (volume ratio) and lithium hexafluorophosphate (LiPF6 1 M) were injected into the assembled battery to prepare a preliminary lithium secondary battery.
[0219] (3) Preparation of lithium secondary batteries
[0220] The activation process was performed by charging the prepared lithium secondary battery to 4.2 V by applying a current at a current rate of 1.0 C at 25° C., and then discharging it to 2.5 V at 0.5 C.
[0221] Comparative Example 4: Preparation of lithium secondary battery
[0222] (1) Preparation of positive electrode
[0223] Will Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 is used as a positive electrode active material. The positive electrode active material is a plurality of (more than 10) Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01]O2 primary particles are combined with each other to form secondary particles, and the average particle size of the secondary particles is D 50 A positive electrode was prepared, the positive electrode comprising a prepared positive electrode active material layer and an aluminum foil (thickness: 12 μm) as a positive electrode current collector, the prepared positive electrode active material layer comprising the positive electrode active material, PVdF as a positive electrode binder, and carbon nanotubes as a positive electrode conductive material in a weight ratio of 98:1:1. The loading capacity of the prepared positive electrode active material layer was 4.5 mAh / cm 2 And the thickness is 140 μm.
[0224] The positive electrode and a lithium metal counter electrode opposite to the positive electrode are prepared, a polyethylene separator is set between the positive electrode and the lithium metal counter electrode, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), lithium hexafluorophosphate (LiPF6 1 M)) is injected to prepare a pre-lithiation battery.
[0225] An electrochemical charger and discharger was connected to the pre-lithiation battery, and the positive electrode was overlithiated by electrochemically charging the pre-lithiation battery at 0.1 C to reach 120% of the charge capacity of the positive electrode.
[0226] (2) Preparation of lithium secondary batteries
[0227] The average particle size D 50 Silicon particles with a diameter of 5 μm are used as negative electrode active materials. A negative electrode is prepared, the negative electrode comprising a preliminary negative electrode active material layer, the preliminary negative electrode active material layer comprising the negative electrode active material, CMC as a negative electrode binder, and carbon nanotubes as a negative electrode conductive material in a weight ratio of 80:10:10. The loading amount of the preliminary negative electrode active material layer is 10 mAh / cm 2 And the thickness is 75 μm.
[0228] The positive electrode prepared in (1), the negative electrode and the porous polyethylene separator were assembled using a winding method, and a preliminary lithium secondary battery was prepared by injecting an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), lithium hexafluorophosphate (LiPF6 1 M)) into the assembled battery and leaving the assembled battery alone for 48 hours.
[0229] (3) Preparation of lithium secondary batteries
[0230] The preliminary lithium secondary battery was charged to 4.2 V by applying a current at a current rate of 1.0 C at 25° C. and then discharged to 2.5 V at 0.5 C to perform an activation process, thereby forming a solid electrolyte layer on the negative electrode.
[0231] Experimental Example 1: Confirmation of A value
[0232] The A values of the lithium secondary batteries of Examples and Comparative Examples were confirmed in the following manner.
[0233] [Mathematical formula 1]
[0234] A = {(F+C) / (F+C+G+M+E)}×100
[0235] Where F and C are the contents of fluorinated groups (unit: μg / cm 2 ) and carbonate group content (unit: μg / cm 2 ), which was confirmed by capillary electrophoresis (CE) analysis of the solid electrolyte layer, and
[0236] G, M and E are the contents of ethylene glycol groups (unit: μg / cm 2 ), methyl content (unit: μg / cm 2 ) and ethyl content (unit: μg / cm 2 ), which was confirmed by nuclear magnetic resonance (NMR) spectroscopy analysis of the solid electrolyte layer.
[0237] Experimental Example 2: Confirmation of L value
[0238] The L values of the lithium secondary batteries of Examples and Comparative Examples were confirmed in the following manner.
[0239] L = L2 / L1
[0240] where L1 and L2 are the integral values of the lithium peak in the graph obtained by laser induced breakdown spectroscopy (LIBS),
[0241] wherein L1 is measured at the interface between the negative electrode active material layer and the negative electrode current collector, and
[0242] L2 is measured at a point at a distance of 20% of the thickness of the negative electrode active material layer in the thickness direction from the interface between the negative electrode active material layer and the solid electrolyte layer.
[0243] Experimental Example 3: Confirmation of initial capacity
[0244] The initial capacities of the lithium secondary batteries of Examples and Comparative Examples were confirmed in the following manner.
[0245] Specifically, the lithium secondary battery was charged to 4.2 V at a current rate of 1 C, and discharged to 2.5 V at a current rate of 0.5 C to confirm the capacity during discharge.
[0246] Experimental Example 4: Confirmation of Initial Resistance
[0247] The initial resistance of the lithium secondary batteries of Examples and Comparative Examples was confirmed in the following manner.
[0248] After the lithium secondary battery was charged and discharged, the lithium secondary battery was fully charged again and then discharged to a state of charge (SOC) of 50%. Then, a 2.5C pulse current was applied for 30 seconds, and the resistance value was obtained by dividing the difference between the voltage before the current application and the voltage 10 seconds after the current application by the current value.
[0249] Experimental Example 5: Confirmation of Capacity Retention Rate
[0250] The capacity retention ratio was confirmed in the following manner by charging and discharging the lithium secondary batteries of the examples and comparative examples, respectively.
[0251] Charging conditions: Charge to 4.2V at 1C current rate
[0252] Discharge conditions: Discharge to 3.0V at a current rate of 0.5C
[0253] Each capacity retention rate was derived by the following calculation.
[0254] Capacity retention rate (%) = (100th discharge capacity / 1st discharge capacity) × 100
[0255]
[0256] Referring to Table 1, compared with Comparative Examples 1 and 2 in which the A value is less than 10%, it can be understood that Examples 1 to 5 in which the A value is 10% or more have higher initial capacity and capacity retention rate and lower battery resistance. In addition, for Comparative Example 3 in which the negative electrode is pre-lithiated, the A value is less than 10% due to the increase in organic components in the solid electrolyte layer and the excessive occurrence of cracking of the negative electrode active material particles on the surface of the negative electrode, and it can be confirmed that the resistance is high due to the thin and uneven initial solid electrolyte layer, and also causes the problem of reduced capacity and life.
[0257] In addition, for Comparative Example 4 in which lithium is embedded in the positive electrode by an electrochemical method using a pre-lithiation method, it can be understood that due to the low content of inorganic components in the solid electrolyte layer, unlike the transfer method according to the present invention, it is difficult to form a thin and stable solid electrolyte layer, and therefore, it can be confirmed that it has an adverse effect on capacity and life characteristics.
[0258] [reference numerals]
[0259] 300: Transfer stack
[0260] 310: Base film
[0261] 320: Lithium metal layer
[0262] 330: Polymer layer
[0263] 100: Positive
[0264] 110: Positive electrode collector
[0265] 120': Preparing positive electrode active material layer
[0266] 400: Positive electrode structure
[0267] R: Roller
Claims
1. A lithium secondary battery, comprising: A positive electrode, the positive electrode comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector; A negative electrode, the negative electrode comprising a negative electrode current collector, a negative electrode active material layer disposed on the negative electrode current collector, and a solid electrolyte layer disposed on the negative electrode active material layer; A separator disposed between the positive electrode and the negative electrode; and Electrolytes, According to formula 1, the value of A is greater than 10%. [Mathematical formula 1] A = {(F+C) / (F+C+G+M+E)}×100 Where F and C are the contents of fluorinated groups (unit: μg / cm 2 ) and carbonate group content (unit: μg / cm 2 ), which is confirmed by capillary electrophoresis analysis of the solid electrolyte layer, and G, M and E are the contents of ethylene glycol groups (unit: μg / cm 2 ), methyl content (unit: μg / cm 2 ) and ethyl content (unit: μg / cm 2 ), which was confirmed by nuclear magnetic resonance (NMR) spectroscopy analysis of the solid electrolyte layer.
2. The lithium secondary battery according to claim 1, wherein the L value according to Mathematical Formula 2 is 45% or more, [Mathematical formula 2] L = L2 / L1 where L1 and L2 are the integral values of the lithium peak in the graph obtained by laser induced breakdown spectroscopy (LIBS), wherein L1 is measured at the interface between the negative electrode active material layer and the negative electrode current collector, and L2 is measured at a point at a distance of 20% of the thickness of the negative electrode active material layer in the thickness direction from the interface between the negative electrode active material layer and the solid electrolyte layer.
3. The lithium secondary battery according to claim 1, wherein the negative electrode active material layer comprises negative electrode active material particles, and The negative electrode active material particles include silicon-based negative electrode active material particles.
4. The lithium secondary battery according to claim 1, wherein Mathematical Formula 3 is satisfied, [Mathematical formula 3] 1.2 ≤ I [003] / I [200] ≤ 2.0 in, In mathematical formula 3, I [003] is the integrated value of the maximum peak appearing in the 2θ range of 17.0° to 19.0° during X-ray diffraction (XRD) measurement of the surface of the positive electrode active material layer, and I [200] It is an integrated value of the maximum peak appearing in the 2θ range of 43° to 45° during XRD measurement of the surface of the positive electrode active material layer. 5 . The lithium secondary battery according to claim 1 , wherein the positive electrode active material layer comprises at least one selected from the group consisting of Li 3 N, Li 2 CO 3 , and LiOH. 6 . The lithium secondary battery according to claim 1 , wherein the positive electrode further comprises a lithium metal layer disposed on the positive electrode active material layer.
7. A method for preparing a lithium secondary battery, the method comprising: Step B1: preparing a preliminary lithium secondary battery, the preliminary lithium secondary battery comprising: a positive electrode, the positive electrode comprising a positive electrode collector and a positive electrode active material layer disposed on the positive electrode collector; a negative electrode, the negative electrode comprising a negative electrode collector, a negative electrode active material layer disposed on the negative electrode collector and a solid electrolyte layer disposed on the negative electrode active material layer; a separator disposed between the positive electrode and the negative electrode; and electrolytes, and Step B2: activating the prepared lithium secondary battery, The method for preparing the positive electrode comprises: Step P1: Arranging a transfer stack on a preliminary positive electrode including a preliminary positive electrode active material layer to form a positive electrode structure, wherein the transfer stack comprises a substrate film and a lithium metal layer arranged on the substrate film, so that the lithium metal layer and the preliminary positive electrode active material layer are in contact with each other; Step P2: rolling the positive electrode structure; and Step P3: preparing a positive electrode by removing the substrate film from the transfer stack after the calendering, Wherein step B2 includes charging the prepared lithium secondary battery by applying a current at a current rate of 0.1C to 1C to the prepared lithium secondary battery. 8 . The method according to claim 7 , wherein a current rate of the current applied to the prepared lithium secondary battery in step B2 is in a range of 0.1C to 0.7C.
9. The method according to claim 7, wherein step B2 is performed at a temperature of 15°C to 85°C.
10. The method according to claim 7, further comprising after step P2: Step P4: placing the prepared positive electrode alone for 1 minute to 600 minutes.
11. The method according to claim 7, wherein: In step P2, The calendering is performed by a roll pressing method. 12 . The method according to claim 7 , wherein the lithium metal layer has a thickness of 1 μm to 10 μm. 13 . The method according to claim 7 , wherein a loading amount of the lithium metal layer is 4% to 40% of a loading amount of the preliminary positive electrode active material layer.
14. The method of claim 7, wherein the transfer stack further comprises a polymer layer, and The polymer layer is provided between the base film and the lithium metal layer. 15 . The method according to claim 7 , wherein a pressure applied to the positive electrode structure during the rolling is in a range of 10 kgf / cm to 90 kgf / cm.
Citation Information
Patent Citations
Manufacturing method of Graphene Quantum Dot / Silicone/Carbon nanomaterials Composites as Anode Materials for Lithiumion Batteries and Manufacturing method for Lithiumion Batteries using it
KR1020220106403A